PELATIHAN CANVA SEBAGAI UPAYA PENGEMBANGAN DIRI DAN PENGENALAN LITERASI DIGITAL BAGI KALANGAN REMAJA MASJID - Sugeng Murdowo Murdowo; Wahjono Wahjono Wahjono; Wafi Arifin Arifin; Syahrul Afrianto Afrianto; Desta Surya Rizki; Fata Nidaul Khasanah (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2025)
The implementation of digital literacy programs has become essential amidst the increasing intensity of internet usage in society. Several challenges are faced by the community partners, including a lack of knowledge and understanding of digital literacy, the absence of adequate facilities and infrastructure to support a digital literacy culture through the creation of positive content, and the unavailability of self-development programs to foster creativity among mosque youth. The aim of this initiative is to optimize the role of mosque youth by actively engaging them in digital literacy activities. The methods of implementation include observation, program socialization, training, provision of supporting facilities and infrastructure, mentoring, and evaluation. As a result of the program, the implementing team established a digital literacy space equipped with supporting facilities and infrastructure. To enhance participants' knowledge, the team conducted knowledge-sharing sessions on digital literacy and soft skills training on how to use Canva to create positive digital content for mosque youth. Evaluation through group discussions revealed a high level of enthusiasm from the participants throughout the training activities. Results from the assessment questionnaire showed that the community partners found the program and the provided facilities to be highly beneficial in supporting digital literacy activities, with a satisfaction rate of 100%.